2013
DOI: 10.1063/1.4794753
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional flow structure and aerodynamic loading on a revolving wing

Abstract: A numerical study is conducted to examine the vortex structure and aerodynamic loading on a revolving wing in quiescent flow. A high-fidelity, implicit large eddy simulation technique is employed to simulate a revolving wing configuration consisting of a single, aspect-ratio-one rectangular plate extended out a distance of half a chord from the rotational axis at a fixed angle relative to the axis. Shortly after the onset of the motion, the rotating wing generates a coherent vortex system along the leading-edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 35 publications
11
59
0
Order By: Relevance
“…This configuration is similar to that reported in Garmann et al 22 except that they considered a 4% thickness wing and initiated the rotation using Eldredge's function (whereas we apply an impulsive start, i.e. step function).…”
Section: Ivb2 Revolving Wingsupporting
confidence: 59%
See 1 more Smart Citation
“…This configuration is similar to that reported in Garmann et al 22 except that they considered a 4% thickness wing and initiated the rotation using Eldredge's function (whereas we apply an impulsive start, i.e. step function).…”
Section: Ivb2 Revolving Wingsupporting
confidence: 59%
“…step function). Figure 10 compares results obtained using the IBLGF method with those obtained by Garmann et al 22 Good agreement is observed between both approaches with some discrepancies that may partly arise from wing thickness and acceleration profile. Note that values in Garmann et al…”
Section: Ivb2 Revolving Wingsupporting
confidence: 53%
“…A stable LEV grows in the direction in which the vorticity is extracted. The vorticity and circulation of the LEV can significantly increase the lift and thus it is exploited on both man-made and natural flyers [3,4,5,6]. Remarkably, it has been identified across a wide range of Re.…”
Section: The Leading Edge Vortexmentioning
confidence: 99%
“…Though bird flight and landing is a three-dimensional problem, two-dimensional flow topologies often dominate in highly unsteady manoeuvres, as was shown by Garmann et al (2013), and so we restrict ourselves to the two-dimensional pitch-up problem.…”
Section: Introductionmentioning
confidence: 99%